No. 1 2-SON DEKABR, 2025 -YIL CRM -MANAGEMENT IN CHAIN ​​SUPERMARKETS IN DEVELOPING COUNTRIES: THE ROLE OF CUSTOMER DATA, LOYALTY PROGRAMS AND OMNICHANNEL STRATEGIES IN INCREASING THE EFFICIENCY OF RETAIL TRADE (Marketing Journal, 2025)
This article analyzes the role of customer data, loyalty programs, and omnichannel strategies in enhancing CRM management efficiency in chain supermarkets in developing countries. Key CLV indicators and their relevance in personalizing № 1 306 customer experience are discussed. The impact of contextual factors –such as cash - dominated payments, uneven digital infrastructure, and logistical limitations –on CRM implementation is assessed. The research methodology is based on a systematic literature review and secondary data analysis. A conceptual CRM model adapted to the context of Central Asia has been developed. Practical recommendations are presented for integrating CRM systems and improving retail performance. The findings can be applied by retailers to optimize marketing strategies and customer engagement.
Keywords: CRM management; customer data; CLV; omnichannel; loyalty programs; retail; developing markets; e -commerce; supermarket; personalization